Deconstructing the value proposition of an innovation exemplar. Issue 1 (4th February 2014) - Payne, Adrian; Frow, Pennie
Abstract : Purpose: – Research into the identification and development of value propositions has recently been identified as a key research priority by the Marketing Science Institute. The purpose of this article is to identify and develop a process for value proposition deconstruction that can help organizations transform their value propositions in order to gain an improvement in their competitive position. Design/methodology/approach: – A case study of an exemplar organization in the health care sector is used to develop an approach for value proposition deconstruction. Using the business system concept as a theoretical framework, the key value-adding elements that comprise this organization's value proposition are identified. A leading financial services firm is used to demonstrate how this learning approach can be successfully applied in developing a new and innovative value proposition. Findings: – Using the business system framework, a structured process for deconstructing value propositions is developed. This framework is extended to explicitly acknowledge the value-in-use that results from different encounters, to incorporate learning processes and to recognize its interactive and recursive nature. Practical implications: – The authors provide practitioners with insight into how to formulate new or improved value propositions. Originality/value: – This work addresses two important and previously unaddressed research questions: how can the process of deconstruction of an exemplar organization's value proposition provide a more comprehensive understanding of the elements that comprise a superior value offering; and how can this process be applied to other organizations seeking to improve their value proposition?